2014
DOI: 10.21608/jpp.2014.53662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grafting on the Cucumber Yield and Quality Under High and Low Temperatures.

Abstract: Two experiments were conducted during the summer and winter seasons of 2013 to study the effect of grafting using different rootstocks on the yield and quality and chemical analysis of cucumber (Cucumis sativus L.) cultivar "Hady" under high and low temperatures. The experiments consisted of 5 treatments, 4 rootstocks, namely Bottle Gourd (Lagenaria siceraria Standl.), Supper Shintosa (Cucurbita maxima Duchesne×Cucurbita moschata Duchesne), Squash 3 (Cucurbita pepo) and Ferro' (C. maxima × C. moschata), in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In this concern, many authors proved that grafting affected fruit yield of cucumber Mady (2009). Besides, El-Sayed et al, (2014) who stated that grafting increased early and total yield of cucumber fruits. Also, these results are supported by the findings of Barnett et al (1990).…”
Section: -Effect Of Grafting and Some Foliar Applications On Cucumbementioning
confidence: 99%
“…In this concern, many authors proved that grafting affected fruit yield of cucumber Mady (2009). Besides, El-Sayed et al, (2014) who stated that grafting increased early and total yield of cucumber fruits. Also, these results are supported by the findings of Barnett et al (1990).…”
Section: -Effect Of Grafting and Some Foliar Applications On Cucumbementioning
confidence: 99%
“…Pumpkin rootstock PI599586 in both years exhibited the highest significant TSS%. Several former studies recorded increment in average fruit weight trait (El-Sayed et al, 2014…”
Section: Effect Of Different Rootstocks On Fruit Quality Traitsmentioning
confidence: 99%
“…Owing to using genetically different rootstocks all the studied characteristics were significantly affected by type of rootstocks used for grafting. El-Sayed et al (2014) who indicated that the effect of grafting using different rootstocks on cucumber (Cucumis sativus L.) cultivar "Hady" in winter season caused a significant increase in plant height over self-grafted control plants. The results indicated that Ferro rootstock increased plant heightof cucumber in summer and winter seasons as compared with un-grafted control.…”
Section: The Effect Of Interaction Between Squash Hybrids and Rootstocksmentioning
confidence: 99%
“…Grafting of cucumber on four different rootstocks namely Bottle Gourd (Lagenaria siceraria Standl. ), Supper Shintosa (Cucurbita maxima Duchesne×Cucurbita moschata Duchesne), Squash 3 (Cucurbita pepo) and Ferro (C. maxima × C. moschata) resulted in an increase in cucumber plant height when grafted on Ferro rootstock in both summer and winter seasons, compared with (control) and other rootstocks used (El-Sayed et al, 2014).Rootstocks considered as powerful of supply water and nutrient uptake by the soil leads to distribute growth regulators to the grafted parts (Helaly, 2017). The effect of grafting on cucumber, watermelon and melon plants grafted onto Cucurbita spp.…”
Section: Introductionmentioning
confidence: 99%